A framework to analyse the efficiency and governance of zakat institutions - Abd. Wahab, Norazlina; Abd Rahman, Abdul Rahim (Emerald Group Publishing Limited, 2011)
Purpose – This paper aims to present a conceptual model on the efficiency and governance of zakat institutions that are responsible in collecting, managing and distributing zakat in Malaysia.Zakat is an Islamic religious “tax” charged on the rich and well-to-do members of the community for distribution to the poor and the needy as well as other beneficiaries based on certain established criteria according to the Qur'an. The main aim of zakat is to protect the socio-economic welfare of the poor and the needy.Design/methodology/approach – The paper reviews and synthesises the relevant literature on efficiency, governance and zakat. The paper then developed and proposed a conceptual model to study the efficiency and governance of zakat institutions. Findings – The paper identifies the appropriate methods to evaluate efficiency and governance of zakat institutions. Such evaluations are crucial for the Islamic financial system to function effectively in order to achieve the noble objectives of socio-economic justice through proper distribution of wealth.Originality/value – This paper presents a conceptual model of efficiency and governance of zakat institutions which would be useful for further empirical research in this area.The findings are not only relevant and applicable to Malaysia but also to other Muslim countries.